Simulasi Pergerakan Dana Tabarru Produk Asuransi Jiwa Unit Link Syariah - Indah Gumala Andirasdini; Ratih Suryaningsih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
Premi or known as Contributions in sharia insurance are part of tabbaru fund which is paid by participants. Tabarru’ has puposes to provide the